Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am suppose to solve for P(t), to find an epxression for P(t) and I am suppose to find the limit.

I can't find anything.

$$\frac{dP}{dt} = k(M - P)$$

$$\frac{dP}{M - P} = k \, dt$$

$$\int \frac{dP}{M - P} = \int k \, dt$$ $$ \ln \frac{1}{M - P} = xk + c$$ $$ \frac{1}{M - P} = e^{xk} + e^c$$ $$ \frac{1}{e^{xk} + e^c} = M - P$$ $$ -\frac{1}{e^{xk} + e^c} +M= P$$

This is wrong but I am not sure why.

share|improve this question
add comment

2 Answers

up vote 6 down vote accepted

The separation of variables went well, and in general outline the calculation was along the right lines. However, there are some problems of detail.

An antiderivative of $\frac{dP}{M-P}$ is $-\ln(|M-P|)$. In your work, the minus sign is missing.

It is always good to check by differentiating whether you have integrated right. The derivative of $\ln(M-P)$ with respect to $P$ is $-\frac{1}{M-P}$ (Chain Rule). Not quite the $\frac{1}{M-P}$ that is needed, but the fix is easy.

Later there is a typo, there is an $x$ where $t$ is intended. There is also a problem with the simplification of $e^{kt+c}$. Note that $e^{u+v}=e^u e^v$.

To do things right, we integrate and get $$-\ln(|M-P|)=kt +c.$$ Either multiply both sides by $-1$, and take the exponential of both sides, or exponentiate directly. We do the first. So we have $\ln(|M-P|)=-kt -c$, and therefore $|M-P|=e^{-c}e^{-kt}$, so $M-P=\pm e^{-c}e^{-kt}$.

For simplicity, let $C=\pm e^{-c}$. We then get $P=M-Ce^{-kt}.$ To find the appropriate value of $C$, we need more information, such as an initial condition, the value of $P$ at a certain time $t$, often (but not necessarily) at $t=0$. In particular, if $P(0)=0$, it turns out that $C=M$.

The limit as $t\to\infty$ is easy to find even if we are not given an initial condition. I assume that the constant $k$ is positive. Then, as $t\to\infty$, we have $e^{-kt}\to 0$, so the limit of $P(t)$ is $M$.

share|improve this answer
    
I still get the wrong answer fixing those mistakes though, I need $M - M^{-ekt}$ –  user138246 Jun 18 '12 at 21:50
    
@Jordan: Think about what Andre cited. Reflect, you will find more than you wanted. :-) –  B. S. Jun 18 '12 at 21:57
    
@Jordan: I wrote out one solution. In order to get something like what you mention above, you will need the initial condition $P(0)=0$. Maybe that was a part of the problem that you didn't mention. –  André Nicolas Jun 18 '12 at 22:04
1  
@Jordan: I checked in my Stewart, found the problem. He as assuming without saying so that at the beginning the amount $P(0)$ learned is $0$, which is very reasonable. So $P(0)=M-Ce^0=0$ and therefore $C=M$. –  André Nicolas Jun 18 '12 at 22:32
1  
@Jordan: This is a model of amount learned, presumably from knowing nothing at time $t=0$, though that is not explicit. Our general formula is $P(t)=M-Ce^{-kt}$. Put $t=0$. Then $e^{-kt}=e^0=1$, so $0=P(0)=M-C$. Since $M-C=0$, we have $C=M$. –  André Nicolas Jun 18 '12 at 22:40
show 9 more comments

I don't want to add anything important than André cited but, maybe mine illustrate the problem easier. :-)

$$\frac{dP}{dt} = k(M - P)$$

$$\frac{dP}{M - P} = k \, dt$$

$$\int \frac{dP}{M - P} = \int k \, dt$$ $$ \ln\left| \frac{1}{M - P}\right| = -kt + c$$ $$ \frac{1}{M - P} = e^{-kt+ c}=e^{-kt}.e^c=Ce^{-kt} $$ I think the rest is easy because you did the same above before in the body of question.

share|improve this answer
1  
You need to say $\left|\dfrac{1}{M-P}\right| = Ce^{-kt}$ and $C$ is positive, and then drop the absolute value sign along with the assumption that $C>0$. –  Michael Hardy Jun 19 '12 at 0:21
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.